À propos de quelques structures polyprédicatives comparatives à dominante extensive et/ou intensive - Hajok, Alicja (Studia Romanica Posnaniensia, 2019)
The objective of this study is to discuss the semantic properties of the comparative structures polyprédicatves to dominant extensive and/or intensive. The comparative structures released for the need for this study make it possible to specify the nature of the concept of ‘compariso’.